Radiosensitivitas Pisang cv. Ampyang dan Potensi Penggunaan Iradiasi Gamma untuk Induksi Varian - Reni Indrayanti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
Banana is commonly propagated vegetatively by suckers since most of edible banana are triploid, male sterile andparthenocarpic, use of conventional breeding for banana improvement is diffi cult. Mutation induction and in vitro techniqueare alternative tools for banana improvement. The objectives of this research were (1) to determine radiosensitivity of bananacv. Ampyang against gamma irradiation, and (2) to evaluate performance of plantlets regenerated from gamma irradiatedexplants of banana cv. Ampyang. Explants of in vitro grown shoots were exposed to gamma irradiation at 0, 20, 25, 30, 35,40, 45, and 50 Gy to determine their radiosensitivity. Growth and development of regenerated plantlets were recorded after10 months of proliferation and regeneration periods. The CurveExpert ver. 1.4 analysis results indicated that lethal doses ofirradiation reducing 20% to 50% of shoot growth (LD20-50) were 51.07 - 64.54 Gy. All regenerated plantlets from irradiatedexplants produced less numbers of roots, and some of regenerated plantlets, showed signifi cantly less plantlet fresh weightand height than the control one. Plantlets regenerated from explants irradiated with 25, 40, 50 Gy have longer leaves than thecontrol. The regenerated plantlets from gamma irradiation treatments were successfully transferred into soil and they wouldbe used to evaluate existence of variants among regenerated banana plantlets.Keywords: induced mutation, gamma irradiation, lethal dose (LD20-50)